A Framing Analysis of William A. Gamson on The News: The Death of Ibrahim Qubaisi” in Al-Jazeera and Al-Arabiya - Nafiudin, Mukhammad; Basid, Abdul (Universitas Medan Area, 2025)
This study aims to analyze the framing patterns used by Arab media, namely Aljazeera.net and Alarabiya.net, in reporting the death of Hezbollah militia leader Ibrahim Muhammad Qubaisi due to Israeli airstrikes in Lebanon. Using a qualitative content analysis approach based on the framing theory of William A. Gamson, this study analyzes several news articles from both media that discuss the event and Hezbollah's response. The analysis results show that both media use framing devices such as metaphors, catchphrases, exemplars, depictions, visual images, and reasoning devices in the form of root causes, calls to principles, and consequences. Aljazeera.net frames Qubaisi as a martyr and symbol of resistance, while Alarabiya.net highlights his strategic role in Hezbollah's military system. This difference reflects the editorial orientation of each media and affects the construction of the public meaning of the Israel-Hezbollah conflict. This research enriches media framing studies in the Arab world and provides a reference for conflict discourse analysis in the Middle East region.